What’s the Purpose of Higher Education? Proposing Meso-Level Operationalizable Superordinate Strategic Goals for Higher Education Developing the Higher Education Strategy Model and Metrics (HESM & M) (Journal of Education and Development, 2017)
This conceptual paper looks into the question of what purpose and which superordinate strategic goals can be identified for higher education. Because of the large variety of different purposes and goals in the existing literature, there’s a need for integrative models and frameworks that help to manage the complex challenges which higher education is facing in an increasingly complex world. Based on the theoretical perspective of Service Dominant Logic (SD-logic), a holistic higher education strategy system model is presented, allowing higher education decision makers and managers a better understanding and consequently the measurement of strategical higher education goals. Irrespective of the branch of study, the HESM can be used as a decision- making aid in operative tasks regarding curriculum creation and optimization of teaching and learning contents.